2018
DOI: 10.1021/acssuschemeng.7b04697
|View full text |Cite
|
Sign up to set email alerts
|

A Green Route to a Low Cost Anisotropic MoS2/Poly(Vinylidene Fluoride) Nanocomposite with Ultrahigh Electroactive Phase and Improved Electrical and Mechanical Properties

Abstract: Environment issues due to growing energy consumption have motivated great research efforts on new materials for efficient energy storage and their low cost fabrication. This study reports an energy-efficient solution route for the fabrication of a unique high permittivity nanocomposite film consisting of molybdenum disulfide (MoS2) nanosheets spontaneously aligned in poly­(vinylidene fluoride) (PVDF) via super-2D-confinement and gravity sedimentation. A simple thermal lamination was further developed to get an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…Furthermore, since MoS 2 nanoflowers with abundant single and few layers exhibit strong piezoelectric potential at the edge sites, their incorporation in PVDF may also contribute to the overall enhanced piezoelectricity of the composite film through a synergistic effect [ 8 , 11 ]. This morphology dependent interaction of MoS 2 is highlighted by the fact that primarily γ and α phase has been reported in MoS 2 nanotube doped PVDF [ 36 ] while MoS 2 nanosheets induced β phase in PVDF by synergistic electrostatic interaction [ 27 , 28 ]. Thus, in the present case, both inherent piezoelectricity and morphology of MoS 2 nanoflower plays important role in the piezoelectric property of the composite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, since MoS 2 nanoflowers with abundant single and few layers exhibit strong piezoelectric potential at the edge sites, their incorporation in PVDF may also contribute to the overall enhanced piezoelectricity of the composite film through a synergistic effect [ 8 , 11 ]. This morphology dependent interaction of MoS 2 is highlighted by the fact that primarily γ and α phase has been reported in MoS 2 nanotube doped PVDF [ 36 ] while MoS 2 nanosheets induced β phase in PVDF by synergistic electrostatic interaction [ 27 , 28 ]. Thus, in the present case, both inherent piezoelectricity and morphology of MoS 2 nanoflower plays important role in the piezoelectric property of the composite.…”
Section: Resultsmentioning
confidence: 99%
“…PVDF polymer has been well known for its robustness, chemical inertness and piezoelectricity, which therefore would be an ideal candidate to act as a substrate for arresting MoS 2 nanoflowers. The MoS 2 -PVDF based nanocomposites reported so far mainly focussed on energy harvesting applications rather than dye degradation, for example, Cai et al [ 27 ], studied mainly MoS 2 nanosheet induced β phase transformation and mechanical aspects of PVDF films. Maity et al [ 28 ], showed nanogenerator and sensing performance with salt exfoliated bulk MoS 2 and electrospun PVDF composite.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, how to produce high content b-phase and improve its properties has always been a matter of great concern. [15][16][17][18] It is well known that copolymerization is an efficient way to produce b-PVDF with TTT conformation. The introduction of comonomers with a large steric hindrance such as triuoroethylene (TrFE), chloride triuoride ethylene (CTFE), hexa-uoropropene (HFP) and others increases the conformational potential energy of the TGTG 0 conformation chains in the aphase structure.…”
Section: Introductionmentioning
confidence: 99%
“…In a PVDF‐TrFE‐g‐SPS, the strong dipole between H (−72.8 kJ mol −1 ) and F (−328.2 kJ mol −1 ) in PVDF‐TrFE [ 50 ] is known to interact with another strong dipole between Mo (−72.1 kJ mol −1 ) and S (−200.4 kJ mol −1 ) of MoS 2 the nanosheet, [ 51,52 ] causing PVDF‐TrFE backbone chains to rest on the surface of the nanosheets. [ 53–55 ] Under these conditions, the grafted hydrophilic SPS chains with numerous negatively charged sulfonated groups are dangled on the surface of the MoS 2 nanosheets, as schematically shown in Figure 2g. The grafted SPSs are expected to repel each other owing to the negative charges in a chain, making the chains somewhat stretched from the nanosheet surface.…”
Section: Resultsmentioning
confidence: 99%